Nonhuman and Human 'Victims' and 'Perpetrators': Intra-active InSecurity Becomings of the Ebola Outbreak - Theresa Ammann (The Royal Danish Library, 2018)
Although feminist theory and security studies have long criticized post-war gendered meta-narratives that categorize people as either victims or perpetrators based on their (imagined) insecurities, these criticisms have mainly focused on the agency of humans, but have dismissed nonhuman entities as irrelevant. This article explores this binary by assessing the victim- and perpetrator-hood dynamics of nonhuman and human matter during the Ebola outbreak in Liberia. Drawing on Karen Barad’s agential realism, I assess these dynamics by means of three vignettes of inSecurity becoming in peri-urban Liberia. The vignettes are based on ethnographic fieldwork, individual and focus-group interviews, and solicited diaries. This agential realist exploration provides the following new insights into understandings of victim- and perpetrator-hood: (1) nonhuman entities can emerge as victims and perpetrators; (2) victim- and perpetrator-hood are not exclusive states of existence but relational processes of intra-actively emerging becomings; and (3) both insecurity and security emerge concurrently through the entangled becoming of victim and perpetrator. These insights require further research to reconsider concepts such as intentionality, responsibility and ethics in discussions of war, post-conflict justice and humanitarian and peacebuilding efforts.